1988
DOI: 10.1007/bf00043378
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal glycoalkaloids in tubers and leaves of Solanum species used in potato breeding

Abstract: The compositions of glycosidic-bound steroidal alkaloids (SA) of Solanum species used in potato breeding were assessed by capillary gas chromatography using simultaneous nitrogen-specific (NPD) and flameionisation detection (FID) . High concentrations of solanidine glycosides and other steroidal glycoalkaloids, amongst which the teratogenic SA solasodine, were found in tubers and leaves of wild species . In addition unidentified compounds were found, which were most probably SA as was shown by their NPD/FID re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Van Gelder et al (1988) concluded that this required further study in wild species. It is also important in early maturing commercial cultivars where there is a strong market demand for small tubers harvested before the plants mature and senesce.…”
Section: Introductionmentioning
confidence: 93%
“…Van Gelder et al (1988) concluded that this required further study in wild species. It is also important in early maturing commercial cultivars where there is a strong market demand for small tubers harvested before the plants mature and senesce.…”
Section: Introductionmentioning
confidence: 93%
“…(1976), Sinden et al . (1980), Dimock & Tingey (1985), Gregory (1984), Kuhn & Low (1955), Tingey & Sinden (1982) and van Gelder et al (1988) . Usually, species contained more than one glycoalkaloid, and in our analysis were considered in the calculations for each of these glycoalkaloids .…”
Section: Characteristics Of Wild Potato Speciesmentioning
confidence: 99%
“…Wild potatoes contain a variety of glycoalkaloids, often in concentrations far greater than observed in cultivated potatoes (van Gelder et al ., 1988) . Excessive total glycoalkaloids are associated with undesirable flavor and mammalian toxicity and teratogenicity (Gregory et al ., 1981) .…”
Section: Glycoalkaloid Contentmentioning
confidence: 99%
“…Therefore low levels of glycoalkaloids in the tubers are a prerequisite. The expression of glycoalkaloids may differ between leaves and tuber of a potato plant, as was reported by Gelder et al (1988) and Friedman (2006), which may open possibilities for breeding varieties with high levels of glycoalkaloids in the leaves and low levels in the tubers.…”
Section: Considerations In Choosing Specific Wild Relatives As Donor mentioning
confidence: 62%
“…Tomatine and aglycone solanidine, two other glycoalkaloid, have also been reported for their role in resistance to CPB (Barbour and Kennedy 1991;Kowalski et al 2000). Tomatine is present in many Solanum species (Gelder et al 1988), including tuber-bearing wild relatives of potato such as S. okadae (Pelletier et al 2001) and S. neocardenasii (Dimock et al 1986).…”
Section: Resistance Breeding Using Natural Variationmentioning
confidence: 99%